Media and Public Relation Through the ERASE Model to Socialize a New Image to the Public in Maintaining the Reputation of the University of Lampung - Utaridah, Nanda; Fardiyan, Ahmad Rudy; Prasetya, Vito; Wibawa, Agung (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
Crisis communication can occur in any organization, including the State University of Lampung University. This campus has always had a good reputation in the eyes of the public, but when the bribery case occurred, the public's trust in Unila was disappointed, embarrassed and protested. This news spread widely and quickly in the digital era, in less than 24 hours, Unila's news had become a trending topic in society which ultimately formed public opinion. Concepts that are relevant to this research are crisis communication management and public relations media relations to overcome reputation problems. This research aims to find out how Unila Public Relations media promotes a new image to the public in maintaining reputation. Data collection techniques were carried out by observing online media publications and interviews. The research results of 17 news reports using the ERASE model, namely (Evaluation, Research, Action, Strategy and Evaluation), explained that the first evaluation was an introspection process on Unila's previous management system. The results of research on public opinion in online media regarding reporting on the PMB bribery case in 2022 were mostly negative. The action stage is the launching of Unila's new program as an action to change the PMB system rules in 2023 with the tagline PROACTIVE and Be Strong as the new image of the University of Lampung. Next, the PR strategy manages writing or media content and selects media that is right on target, quickly accepted by the public, especially generation Z on TikTok social media. Finally, an evaluation of the results of the implementation of Unila's new program saw an increase in interest in joining Unila, amounting to 18% of the number of students in the previous year.